Perswazyjność wypowiedzi Lecha Wałęsy (na przykładzie wybranych telewizyjnych programów publicystycznych) - Grzegorzewski, Krzysztof (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2009)
Author analyses public saying of the former president, Lech Wałęsa, in two selected TV-programs, broadcasted in similar period of time, but in two different TV-stations. Analysis constitutes a try of codification of all the stylistic and linguistic tricks and rethorical mechanisms of content, and also valuation of its persuastic use. On the basis of this analysis, author answers the following question: Is the language correctness a necessary condition of the persuasion in politics’ public saying?